Fungos e nematoides associados a sementes de forrageiras tropicais - Mallmann, Guilherme; Verzignassi, Jaqueline Rosemeire; Fernandes, Celso Dornelas; Santos, Jaime Maia Dos [UNESP]; Vechiato, Marta Helena; Inácio, Carlos Antonio; Batista, Margareth Vieira; Queiroz, Carolina De Arruda (Grupo Paulista de Fitopatologia, 2013)
This study aimed to assess the incidence of fungi and nematodes in Brachiaria sp. and Panicum maximum seeds produced in the Brazilian states of Mato Grosso do Sul (MS), Mato Grosso (MT), Goiás (GO), Minas Gerais (MG) and São Paulo (SP). The main fungi found in the seeds were Bipolaris sp., Curvularia sp. and Phoma sp.. The lowest incidence of these fungi was found for seeds of Brachiaria brizantha cultivars BRS Piatã and Xaraés, and Brachiaria decumbens cv. Basilisk, from the states of GO, MG and MS, respectively. The cultivars Marandu and BRS Piatã, from several regions, exhibited high occurrence of Aphelenchoides sp. and Ditylenchus sp.. Seeds of B. humidicola cultivar Humidicola, produced in MS and SP, did not show association with nematodes. The seeds of Panicum maximum cv. Massai and cv. Mombaça showed higher incidence of Bipolaris sp., Cladosporium sp., Curvularia sp., Fusarium sp. and Phoma sp., as well as Aphelenchoides sp. and Ditylenchus sp., especially for seeds produced in MT. Some of the detected pathogens are causative agents of diseases of major importance in forage plants, such as Bipolaris sp., causing leaf spot in Panicum, of high severity in Tanzânia, which provides serious compromising of the pasture sustainability.

Objetivou-se avaliar a incidência de fungos e nematoides em sementes de Brachiaria sp. e Panicum maximum produzidas nos estados de Mato Grosso do Sul (MS), Mato Grosso (MT), Goiás (GO), Minas Gerais (MG) e São Paulo (SP). Os principais fungos encontrados nas sementes foram Bipolaris sp., Curvularia sp. e Phoma sp.. As menores incidências destes fungos foram encontradas nas sementes das cultivares BRS Piatã e Xaraés de Brachiaria brizantha e Brachiaria decumbens cv. Basilisk, oriundas dos estados de GO, MG e MS, respectivamente. As cultivares Marandu e BRS Piatã, provenientes das várias regiões, apresentaram elevada ocorrência de Aphelenchoides sp. e Ditylenchus sp.. Sementes da cultivar Humidicola, de Brachiaria humidicola, produzidas em MS e SP, não apresentaram associação com nematoides. As sementes de Panicum maximum cv. Massai e cv. Mombaça apresentaram maiores incidências de Bipolaris sp., Cladosporium sp., Curvularia sp., Fusarium sp. e Phoma sp., bem como de Aphelenchoides sp. e Ditylenchus sp., especialmente nas sementes produzidas em MT. Alguns dos patógenos encontrados são agentes causais de doenças de grande importância em forrageiras, a exemplo de Bipolaris sp., causando a mancha foliar do Panicum, de alta severidade em Tanzânia, proporcionando sérios comprometimentos da sustentabilidade das pastagens.
Fungi and nematodes associated with tropical forage seeds
Keywords: Brachiaria brizantha; Panicum maximum; pathogen; Brachiaria brizantha; Panicum maximum; Patógeno